Body composition of schoolchildren: A comparative analysis - Faitarone Brasilino, Fabricio; Dias de Jesus, Eduarda Eugenia; Valdivia Moral, Pedro Ángel; Cortes Morales, Pedro Jorge (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of the study was to evaluate the body composition of schoolchildren between 6 and 11 years of age, enrolled in elementary school I of municipal schools in a city of Santa Catarina, Brazil. Participated students from 1st to 5th grade. A total of 804 children participated in the sample, 440 girls and 364 boys, aged 6 to 11 years. The research instruments were individual anthropometric measurements for the calculations of Body Mass Index (BMI) and Body Adiposity Index (BAI). For the analysis and interpretation of the data obtained, the statistical program used was SPSS 20.0. The results of the BMI of the sample were 17.7 kg/m² and the BAI was 20.1%. The boys had lower BMI (0.01 less) and BAI (0.03 less) values. When classifying we see that 53% of the sample is "eutrophic", that is, ideal weight according to the BMI values (kg/m²). Likewise for the BAI (%). We observed that 62% of the sample is classified as "eutrophic". We conclude that the students from 6 to 11 years old enrolled from 1st to 5th grade in municipal schools in a city of Santa Catarina are mostly eutrophic.